Predation on cephalopods by Weddell seals, Leptonychotes weddellii, at Hope Bay, Antarctic Peninsula - Daneri, Gustavo Adolfo; Carlini, A. R.; Negri, Agustina; Allcock, A. L.; Corbalán, A. (Polar Biology)
Cephalopods play a key role in marine environments as food resources for top predators such as marine mammals and seabirds. However, detailed information on their trophic relationships with Antarctic seals is scarce. The aim of the present study was to examine the cephalopod portion of the diet of adult and subadult Weddell seals, Leptonychotes weddellii, at Hope Bay, Antarctic Peninsula, through the analysis of scats collected during three consecutive summers (2003, 2004 and 2005). Cephalopods occurred in almost 45% of the 217 samples collected during the whole period of study. A total of 662 beaks (358 upper and 304 lower) were removed from scats containing cephalopod remains (n = 93). Octopods were largely dominant in comparison with teuthoids constituting in numerical abundance over 95% of the cephalopod prey. The octopod Pareledone turqueti was the most frequent and dominant prey species representing, respectively, 57.9 and 71.1% in numbers and biomass of cephalopods consumed. Species belonging to the group of papillated Pareledone were second in importance. The results were compared with information from previous dietary studies of L. weddellii at other localities of Antarctica. Based on the examination of the cephalopod prey taxa identified in this study, it is suggested that during the study period Weddell seal individuals foraged mainly on benthic prey resources close to the coast, in inshore waters where octopods were dominant in comparison with pelagic squid. © 2011 Springer-Verlag. Fil: Daneri, Gustavo Adolfo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Carlini, A. R. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Negri, Agustina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo ...